2017
DOI: 10.1371/journal.pone.0183179
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry as a potential modifier of gene expression in breast tumors from Colombian women

Abstract: BackgroundHispanic/Latino populations are a genetically admixed and heterogeneous group, with variable fractions of European, Indigenous American and African ancestries. The molecular profile of breast cancer has been widely described in non-Hispanic Whites but equivalent knowledge is lacking in Hispanic/Latinas. We have previously reported that the most prevalent breast cancer intrinsic subtype in Colombian women was Luminal B as defined by St. Gallen 2013 criteria. In this study we explored ancestry-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 65 publications
2
20
0
2
Order By: Relevance
“…The results of the current analysis in patients with breast cancer from Peru, and including independent replication in patients from Mexico and Colombia, strongly suggest there could be population-specific genetic variant(s) increasing the risk of HER2 þ tumors among women with IA ancestry. These results are consistent with the previously reported suggestive association between IA ancestry and ERBB2 gene expression (which codes for the HER2 protein) in breast tumors from Colombia (51).…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current analysis in patients with breast cancer from Peru, and including independent replication in patients from Mexico and Colombia, strongly suggest there could be population-specific genetic variant(s) increasing the risk of HER2 þ tumors among women with IA ancestry. These results are consistent with the previously reported suggestive association between IA ancestry and ERBB2 gene expression (which codes for the HER2 protein) in breast tumors from Colombia (51).…”
Section: Discussionsupporting
confidence: 93%
“…These results were confirmed by RT-PCR. In the replication set, the authors found a statistically significant association between ERBB2 expression with IA ancestry (p = 0.02, B = 3.11) [25]. Again, these statistical correlations may reveal biological clues.…”
Section: Luminal B Breast Cancer In Colombiansmentioning
confidence: 84%
“…Following up on these intriguing observations, the same group performed wholetranscriptome RNASeq on 21 immunohistochemically defined luminal A and 21 luminal B tumors from the same 301-patient cohort. Serrano-Gomez et al [25] found 67 differentially expressed genes (p < 0.05) from which 39 were upregulated and 28 downregulated in the luminal B subtype (Fig. 13.1).…”
Section: Luminal B Breast Cancer In Colombiansmentioning
confidence: 97%
“…In the ensuing decade, an increasing number of studies have indicated the involvement of snoRNAs in different tumors, including lymphoma, breast cancer, melanoma, and myeloma [8][9][10][11][12]. It has been reported that snoRNAs are regulated in a was complex manner by host genes, copy number variation, and DNA methylation [13].…”
Section: Introductionmentioning
confidence: 99%